Development of a Randomized Trial Comparing ICP-Monitor-Based Management of Severe Pediatric Traumatic Brain Injury to Management Based on Imaging and Clinical Examination Without ICP Monitoring-Research Algorithms - Chesnut, Randall (2024)
BACKGROUND AND OBJECTIVES: The efficacy of our current approach to incorporating intracranial pressure (ICP) data into pediatric severe traumatic brain injury (sTBI) management is incompletely understood, lacking data from multicenter, prospective, randomized studies. The National Institutes of Health-supported Benchmark Evidence from Latin America-Treatment of Raised Intracranial Pressure-Pediatrics trial will compare outcomes from pediatric sTBI of a management protocol based on ICP monitoring vs 1 based on imaging and clinical examination without monitoring. Because no applicable comprehensive management algorithms for either cohort are available, it was necessary to develop them. METHODS: A consensus conference involving the 21 intensivists and neurosurgeons from the 8 trial sites used Delphi-based methodology to formulate management algorithms for both study cohorts. We included recommendations from the latest Brain Trauma Foundation pediatric sTBI guidelines and the consensus-based adult algorithms (Seattle International Brain Injury Consensus Conference/Consensus Revised Imaging and Clinical Examination) wherever relevant. We used a consensus threshold of 80%. RESULTS: We developed comprehensive management algorithms for monitored and nonmonitored cohort children with sTBI. We defined suspected intracranial hypertension for the nonmonitored group, set minimum number and timing of computed tomography scans, specified minimal age-adjusted mean arterial pressure and cerebral perfusion pressure targets, defined clinical neuroworsening, described minimal requisites for intensive care unit management, produced tiered management algorithms for both groups, and listed treatments not routinely used. CONCLUSION: We will study these protocols in the Benchmark Evidence from Latin America-Treatment of Raised Intracranial Pressure-Pediatrics trial in low- and middle-income countries. Second, we present them here for consideration as prototype pediatric sTBI management algorithms in the absence of published alternatives, acknowledging their limited evidentiary status. Therefore, herein, we describe our study design only, not recommended treatment protocols.